2021
DOI: 10.1093/cid/ciab940
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 Reinfection Associates With Unstable Housing and Occurs in the Presence of Antibodies

Abstract: Background The factors associated with severe acute respiratory coronavirus 2 (SARS-CoV-2) reinfection remain poorly defined. Methods We identified patients with SARS-CoV-2 infection and at least one repeat reverse transcription (RT) – polymerase chain reaction (PCR) result a minimum of 90 days after the initial positive test and prior to January 21, 2021. Those with a repeat positive test were deemed to have reinfection (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…Similar to a recent study, we have seen seropositivity in patients with reinfection. 32 In our cohort, the hospitalization rate was higher in fully vaccinated patients compared with unvaccinated ones. However, given that fully vaccinated patients were older and had a significantly higher number of comorbidities, we considered that the comparison was confounded by these factors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similar to a recent study, we have seen seropositivity in patients with reinfection. 32 In our cohort, the hospitalization rate was higher in fully vaccinated patients compared with unvaccinated ones. However, given that fully vaccinated patients were older and had a significantly higher number of comorbidities, we considered that the comparison was confounded by these factors.…”
Section: Discussionmentioning
confidence: 54%
“…33 Because of logistic limitations (inability to preserve initial samples, limited laboratory resources, cost issues), this approach is less likely to be pursued in clinical practice. 32,33 Therefore, we adapted investigative criteria of the Centers for Disease Control and Prevention to define the reinfected population. 11 This approach allows us to capture a larger cohort of patients but at the risk of possible overestimation of the reinfected patients as prolonged viral shedding can occur for weeks to months after the initial infection.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion rose to 83.3% in those who were vaccinated. Bean et al reported that reinfection occurred in individuals despite the presence of antibodies against SARS-CoV-2 in their sera [ 17 ]. In our series, 64 reinfected patients had available serological results; 39 were positive after the first time of infection and 25 were negative.…”
Section: Discussionmentioning
confidence: 99%
“… 21 ] that was validated by a subsequent empirical finding of 18% reinfection by 275 to 300 d after primary infection [ref. 22 ] and, likewise, predicting a 34% probability of reinfection at ∼450 d after primary infection [ref. 21 ] that was validated by a subsequent empirical finding of 34% breakthrough infection 420 to 480 d after primary vaccination [ref.…”
mentioning
confidence: 99%